Tyrosine Kinase Inhibitors-Induced Arrhythmias: From Molecular Mechanisms, Pharmacokinetics to Therapeutic Strategies - Cheng, Mengfei; Yang, Fang; Liu, Jiahui; Yang, Dan; Zhang, Shuo; Yu, Yang; Jiang, Shuai; Dong, Mei (Frontiers in Cardiovascular Medicine, 2021)
With the development of anti-tumor drugs，Tyrosine kinase inhibitors (TKIs) are an indispensable part of targeted therapy. They can be superior to traditional chemotherapeutic drugs in selectivity, safety and efficacy. However, they have been found associated with serious adverse effects in use, such as myocardial infarction, fluid retention, hypertension and rash. Although TKIs induced arrhythmia with a lower incidence than other cardiovascular diseases, much clinical evidence indicated that adequate attention and management should be provided to patients. This review focus on QT interval prolongation and atrial fibrillation (AF) which are conveniently monitored in clinical practice. We collected the data about TKIs, and analyzed the molecule mechanism, discussed the actual clinical evidence, drug-drug interaction and provided the countermeasures to QT interval prolongation and AF. We also pooled data showed that both QT prolongation and AF are related to their multi-target effects. Hitherto, more than thirty TKIs got approval from FDA, most of the novel drugs with a small sample size in the preclinical trial, risk/benefit assessments are not perfect, which leads to a suspension after listing, like nilotinib. Similarly, vandetanib exhibits the most significant QT prolongation and ibrutinib exhibits the highest incidence in AF, but cannot be got enough attention during treatment.